STUDI PERBANDINGAN SIFAT MINYAK KAYU CENDANA SEMUT (EXOCARPUS LATIFOLIA R.BR.) DAN CENDANA WANGI (SANTALUM ALBUM L.) - Bambang Wiyono; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1990)
The purpose of this research is to compare the oil. properties of cendana semut (Exocarpus latifolia R.Br.) and cendana wiangi (Santalum album L.). The sandalwood oils are obtained by distillation method with cohobation system for 18 hours.Results indicated that the essential oil content of cendana semut is lower than cendana wangi. The cendana semut oil had dark-yellow in colour and slightly thicker. During the early stage of distilling process, the distillate of cendana semut some whitish sediment was formed, presumably consisted of resin. Such sediment was not found during the distilling of cendana wangi. The cendana wangi oil had yellowish appearance and its viscosity was lower than that of cendana semut. Ester number after acetylation and total alcohol content (as santalol) of cendana semut oil was lower than of cendana wangi oil. Colour, viscosity, and resin content in the distillate could be used to differentiate cendana semut from cendana wangi oil.